Developing and implementing mathematical models for the prevalence, incidence and initiation into cocaine use in Ireland - Snel, Anne (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2011)
The National Drug Strategy 2009-2016 under the auspices of the Department of Community, Rural and Gaeltacht Affairs (DCRGA) reported widespread public concern regarding the misuse of cocaine, particularly when combined with other illegal substances, and/or alcohol (DCRGA 2009). In order to ensure best practice in treatment services, it is essential that accurate and up to date prevalence figures of drug use are available, that incidence is monitored as an indicator of trends, that information is available as to what interventions will be most effective in reducing cocaine prevalence and that the dynamics of initiation to cocaine use are better understood.
Keywords: Nursing & Midwifery, Ph.D.; Ph.D. Trinity College Dublin.